Development of a Low Cost, AI Enhanced IoT Home Automation System with Adaptive Energy Management and Predictive Maintenance - , Michael Olumuyiwa Adio; , Olalekan Akeeb Raji; , Jumoke Elizabeth Adio (Archives of Current Research International, 2025)
Today modern homes are increasingly transition from manual systems to automated ones with remote control capabilities as automation technology develops. Conventional home electronic appliance access is strict and requires the user to physically attend to many appliance locations before they can be used. This can be stressful for the elderly and disabled and only offers a limited level of operating ease for everyone. To improve the flexibility of a user's remote access to home appliances, the products' wireless connection features become crucial. Furthermore, as technology advances in the modern period, a growing number of individuals get dependent on automated gadgets that they perceive to be able to improve and simplify their lives, particularly in the workplace. By meeting these requirements, the Internet of Things (IoT) improves people's quality of life. This project, an Internet of Things-based smart home lighting system using an ESP32 microcontroller, is designed to make life easier for people, especially for those who are disabled. The major objective of developing a mobile IoT app-based portable home automation system is to provide remote access and control of household appliances and electronics. The project controls the ON and OFF of electrical appliances using an ESP32 and an Internet of Things remote application server and overall response times are relatively consistent but vary slightly depending on the time of day and the specific test, with the system performing slightly better in the afternoon and night compared to the morning that is there is a lot of traffic on the network service provider in the morning for the system to perform better when compared to performance in the afternoon and night.